Analisis Hukum Pidana Penggelapan Mobil Rental Perspektif Hukum Pidana Dan Hukum Pidana Islam: (Studi Putusan NO. 1517/PID.B/2023/PN MDN) - Ardhana, Rizky Owen; Iwan, Iwan (Jayapangus Press, 2025)
Cases of rental vehicle embezzlement are becoming increasingly prevalent, yet there are no specific legal regulations governing such cases, leading to uncertainty in the enforcement of the law. The purpose of this study is to examine the application of Article 372 and which regulations are appropriate to apply in Case No. 1517/Pid.B/2023/PN Mdn, whether they are appropriate or not in the sentencing of the suspect for the misuse of a four-wheeled vehicle. The type of research used by the researcher is normative legal research. The approach in this study applies the Statute Approach, the Regulatory Approach, and the Conceptual Approach, which provides a perspective in analyzing solutions to problems. The strategy for collecting legal materials in this research uses the method of legal data mining through library research, which is conducted using interpretation of legal materials. The research findings show that in decision No. 1517/Pid.B/2023/PN Mdn, there were problems with the judge's decision in case No. 1517/Pid.B/2023/PN Mdn, including the judge's consideration of one of the elements in the act. The judge applied Article 372, but in the chronology of events, there was an element of Article 378 in the sequence of events. The possession of property obtained through fraudulent means or deceit, which benefits one party and harms another, should have led the court to apply the provisions of Article 378 on fraud, as the sequence of events contained elements of Article 378. The research conclusion indicates that there are no clear legal provisions as a basis for cases of embezzlement of four-wheeled vehicles in the car rental sector, resulting in many individuals engaging in misconduct in such rental activities.